THE CORRELATION BETWEEN PREDISPOSING FACTORS OF MOTHER AND DIARRHEA INCIDENCE AMONG CHILDREN UNDER FIVE YEARS OLD IN KELURAHAN WONOKUSUMO - Nindya Kirana (Universitas Airlangga, 2018)
Diarrheal disease is one of health problems in Indonesian. Diarrhea is one of leading causes of under-five mortality. In Wonokusumo, incidence of diarrhea in 2016 is 352 cases. This study aims to know the relationship between predisposing factors, such as knowledge, attitude and behavior of mothers and the incidence of diarrhea in under-five children. The population is mothers whose babies and toddlers in Rw 02 Kelurahan Wonokusumo. This study has 68 samples determined by simple random sampling. Instruments in this study is a questionnaire, using Chi square test analysis. The result of this research shows that attitude variable has p value = 0.019 <α (0.05), so Ho is rejected. It means there is a significant relationship between mother’s attitude and the incidence of diarrhea. Meanwhile, the behavior variable results p value = 0.003 <α (0.05) so that H0 is rejected. Hence, there is a relationship between mother’s behavior and the incidence of diarrhea. Based on those results, health workers need to improve the understanding of mothers, as well as their attitude, and behavior through health education. Moreover, community outreach is also necessary to empower the community for doing clean and healthy life behavior.